Thromboembolic Complications After Receipt of Prothrombin Complex Concentrate. (December 2021) - Owen, Emily J.; Gibson, Gabrielle A.; Human, Theresa; Wolfe, Rachel
Purpose: Patients presenting with life-threatening bleeding associated with oral anticoagulants (OACs) are challenging with few available treatments. Prothrombin complex concentrate (PCC) is an option for OAC reversal in the setting of life-threatening bleeding with a relatively benign safety profile. Little is known about the risk of developing thromboembolic complications (TEC) in patients receiving PCC who were previously anticoagulated. The aim of this study is to characterize the rate of TEC after receipt of PCC.Methods: All adult patients who received 4-Factor PCC for life-threatening bleeding were retrospectively evaluated over a 2-year time period. Data collected included anticoagulant and indication, bleeding source, PCC dose, INR, and TEC within 14 days of PCC dose, including venous thromboembolism (VTE), acute myocardial infarction, and ischemic stroke.Results: Three hundred thirty-three patients received 383 PCC doses. Of these, 55 (16.5%) patients developed TEC, including VTE, ischemic stroke, and acute myocardial infarction. There was increased rivaroxaban use in patients who developed TEC (25.4% vs 12.2%; P = .011). Additionally, there were more patients who had anticoagulation for a previous TEC in those who developed a new TEC (38.2% vs 23.4%; P = .022). Lastly, there was a higher rate of TEC in those who received >1 dose of PCC (21.8% vs 7.9%; P = .002).Conclusion: PCC administration in the setting of life-threatening bleeding is not benign. Risk of TEC increases in patients who have rivaroxaban reversal, receive a repeat dose of PCC, and have a TEC indication for their anticoagulation and these factors should be further investigated.